ISTRI SEBAGAI PENCARI NAFKAH UTAMA DAN DAMPAKNYA DALAM KELUARGA PERSPEKTIF HUKUM ISLAM (Studi Kasus Kehidupan Keluarga TKW di Kabupaten Lampung Timur ) - Bambang Ismanto; Muhammad Rudi Wijaya; Anas Habibi Ritonga (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2018)
The obligation to provide for it is the duty of a husband, but the husband's obligation in reality now borne also by a wife when the husband is not able to provide for the family. A wife chose the path to become migrant workers, which is considered to be able to solve problems of economic problems in the family when the limitations of a husband in meeting the needs of the household. Wife be a shift in the role of migrant workers here between husband and wife as seen from the conditional functional and very clear as happened in East Lampung district, when the wife as the family breadwinner what factors are background wife doing it, and how it impacts the survival household when the wife as the family breadwinner and how Islamic legal review of the wife who become migrant workers. This research is a field research or field research, the research done in the East Lampung Regency. The method used in this research is a case study. Resourch collection techniques in this study is the interviews with informants government officials, religious leaders, members of the families of migrant workers to know the number of migrant workers and the maids how the maid’s family life is family life, including the factors wife become migrant workers. Literature study conducted by studying books and books that relate to a living and about migrant workers to know the problems studied. This study is a descriptive analysis, problem-solving process by describing the problem through the collection of the preparation, analysis, and then described the results of the study showed that there are two factors behind the wife as the family breadwinner to become migrant workers, namely the impact of positive and negative impacts. The positive impact is the requirement for the fulfillment of family life education of children, the fulfillment of decent shelter and also finiset affairs of debts, while the negative impact that a child has a poor attitude, the husband is not responsible for the misuse of remittances and improper management